Entre congruências e incongruências do metatermo Lusofonia - Nogueira Vilarinho, Ricardo Francisco (2021)
In this article we start from two texts, Faraco (2012) and Arakaki and Bastos (2016), extracting from them the definitions of lusophony of Carlos Alberto Faraco, Jose Luiz Fiorin, Armando Jorge Lopes, Eliseu Mabasso and Moises de Lemos Martins. As a tool of analysis, we use the mathematical theory of sets and geometry the concepts of congruence and incongruence. Thus, in the end, we conclude that both linguists describe the same phenomenon, observed from different perspectives, as described by Kuhn (2018).